2023
DOI: 10.3390/atmos14040688
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Factors Driving Carbonate System in Subtropical Coral Community Environments along Dapeng Peninsula, South China Sea

Abstract: Coral reef ecosystems have extremely high primary productivity and play an important role in the marine carbon cycle. However, due to the high carbon metabolism efficiency of coral communities, little is known about the carbon sink–source properties of coral reefs. In November 2022, in situ field investigations coupled with incubation experiments were conducted in typical subtropical coral reef waters, i.e., Yangmeikeng Sea Area (Area I) and Dalu Bay (Area Ⅱ), to explore the dynamics of the carbonate system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…column of the DAB, DLB, and YMKSA by 0.16 ± 0.03 µmol kg −1 , 0.03 ± 0.01 µmol kg −1 , and 0.21 ± 0.04 µmol kg −1 per month; correspondingly, this process increased the DIC by 3.57 ± 0.54 µmol kg −1 , 0.81 ± 0.12 µmol kg −1 , and 4.65 ± 0.70 µmol kg −1 , respectively. A previous study indicated that, in autumn, the microbial respiration of seawater in here can simultaneously reduce the concentration of TA by 14.4-22.8 µmol kg −1 and increase the concentration of DIC by 90.0-168 µmol kg −1 per month [28]. In comparison, the effect of coral metabolism on TA and DIC was much lower than that of microbial respiration.…”
Section: Photosynthesis and Respirationmentioning
confidence: 54%
See 1 more Smart Citation
“…column of the DAB, DLB, and YMKSA by 0.16 ± 0.03 µmol kg −1 , 0.03 ± 0.01 µmol kg −1 , and 0.21 ± 0.04 µmol kg −1 per month; correspondingly, this process increased the DIC by 3.57 ± 0.54 µmol kg −1 , 0.81 ± 0.12 µmol kg −1 , and 4.65 ± 0.70 µmol kg −1 , respectively. A previous study indicated that, in autumn, the microbial respiration of seawater in here can simultaneously reduce the concentration of TA by 14.4-22.8 µmol kg −1 and increase the concentration of DIC by 90.0-168 µmol kg −1 per month [28]. In comparison, the effect of coral metabolism on TA and DIC was much lower than that of microbial respiration.…”
Section: Photosynthesis and Respirationmentioning
confidence: 54%
“…In addition, the focus on coastal coral reef habitats, the metabolic activities of corals, and reef organisms may also have an important effect on the seawater CO 2 system because of the formation of biological calcium carbonate and respiration [27,28]. Generally, coral calcification absorbs total alkalinity (TA) and DIC at a ratio of 2:1 from seawater, resulting in an increase in the pCO 2 and a decrease in the pH and Ω A of the seawater, and vice versa [29].…”
Section: Introductionmentioning
confidence: 99%